Analisis Tingkat Kerentanan Longsor Daerah Muara Sungai Bone Kota Gorontalo - Muhammad Iqbal Asiki; Sri Maryati; Noviar Akase (Universitas Negeri Gorontalo, 2019)
In Gorontalo City there have been 11 landslides in 2017 which are spread in 3 sub-districts namely Hulonthalangi, Kota Barat, and Dumbo Raya. While in 2018 there was a landslide in Tenda village which claimed two lives. The research site is located in coordinate 00°29'00